Linguistic and social aspects of research and studying of scientific terminology (on the material of the Russian and Kazakh languages) (Eurasian Journal of Philology Science and Education, 2016)
The article considers the questions of the modern science about the terms connected with the formation and development of scientific terminology in the Russian and Kazakh languages. The place and the role of the term in the lexical and semantic system of the language, its distinctive signs and functional features are defined. A special place in the article is taken by questions of formation of scientific and technical terminology in the conditions of interaction of languages and cultures. On the material of the language situation in modern Kazakhstan the problems of influence of the Kazakh-Russian bilingualism on linguistic processes of the creation of terms in a scientific and technical discourse are investigated. A special attention in the article is paid to the choice problem of translating scientific texts from one language to another. Linguistic criteria of choosing a way of the formation of the terms are defined: calque translation (literal translation, loan, use of the international term, description, etc.). The conclusion is that the use of the same terms in the Kazakh and Russian languages facilitates studying the vocabulary of both languages.
Keywords: term; terminological system; scientific and technical text; common words; lexical variant; loan; translation.